Kecanggihan Teknologi dan Efektivitas Penggunaan Sistem Informasi Akuntansi dengan Kemampuan Teknik Personal dan Pelatihan sebagai Variabel Pemoderasi - Bagus Vijay Kumara Putra, Putu; Juliarsa, Gede (E-Jurnal Akuntansi, 2021)
The purpose of this study is to empirically examine the effect of technological sophistication on the effectiveness of the use of accounting information systems with personal engineering abilities, and training as a moderating variable. This research was conducted in all hospitals in Denpasar. The number of hospitals in the city of Denpasar is 21 and the number of samples used is 232 people, namely employees in finance and cashiers. The data analysis technique used is Moderated Regression Analysis. The results of this analysis indicate that technological sophistication has a positive effect on the effectiveness of the use of accounting information systems, and training strengthens the influence of technological sophistication on the effectiveness of the use of accounting information systems. Whereas personal technical ability cannot moderate the influence of technological sophistication on the effective use of accounting information systems. Keywords: Technological Sophistication; Personal Technical Ability; Training; Using Accounting Information Systems.